On the possibility of yet a third kinetochore system in the protist phylum Euglenozoa - Benz, Corinna; Raas, Maximilian W D; Tripathi, Pragya; Faktorová, Drahomíra; Tromer, Eelco C; Akiyoshi, Bungo; Lukeš, Julius (mBio, 2024)
UNLABELLED: Transmission of genetic material from one generation to the next is a fundamental feature of all living cells. In eukaryotes, a macromolecular complex called the kinetochore plays crucial roles during chromosome segregation by linking chromosomes to spindle microtubules. Little is known about this process in evolutionarily diverse protists. Within the supergroup Discoba, Euglenozoa forms a speciose group of unicellular flagellates-kinetoplastids, euglenids, and diplonemids. Kinetoplastids have an unconventional kinetochore system, while euglenids have subunits that are conserved among most eukaryotes. For diplonemids, a group of extremely diverse and abundant marine flagellates, it remains unclear what kind of kinetochores are present. Here, we employed deep homology detection protocols using profile-versus-profile Hidden Markov Model searches and AlphaFold-based structural comparisons to detect homologies that might have been previously missed. Interestingly, we still could not detect orthologs for most of the kinetoplastid or canonical kinetochore subunits with few exceptions including a putative centromere-specific histone H3 variant (cenH3/CENP-A), the spindle checkpoint protein Mad2, the chromosomal passenger complex members Aurora and INCENP, and broadly conserved proteins like CLK kinase and the meiotic synaptonemal complex proteins SYCP2/3 that also function at kinetoplastid kinetochores. We examined the localization of five candidate kinetochore-associated proteins in the model diplonemid, Paradiplonema papillatum. PpCENP-A shows discrete dots in the nucleus, implying that it is likely a kinetochore component. PpMad2, PpCLKKKT10/19, PpSYCP2L1KKT17/18, and PpINCENP reside in the nucleus, but no clear kinetochore localization was observed. Altogether, these results point to the possibility that diplonemids evolved a hitherto unknown type of kinetochore system. IMPORTANCE: A macromolecular assembly called the kinetochore is essential for the segregation of genetic material during eukaryotic cell division. Therefore, characterization of kinetochores across species is essential for understanding the mechanisms involved in this key process across the eukaryotic tree of life. In particular, little is known about kinetochores in divergent protists such as Euglenozoa, a group of unicellular flagellates that includes kinetoplastids, euglenids, and diplonemids, the latter being a highly diverse and abundant component of marine plankton. While kinetoplastids have an unconventional kinetochore system and euglenids have a canonical one similar to traditional model eukaryotes, preliminary searches detected neither unconventional nor canonical kinetochore components in diplonemids. Here, we employed state-of-the-art deep homology detection protocols but still could not detect orthologs for the bulk of kinetoplastid-specific nor canonical kinetochore proteins in diplonemids except for a putative centromere-specific histone H3 variant. Our results suggest that diplonemids evolved kinetochores that do not resemble previously known ones.
Keywords: Euglenozoa; Protozoan Proteins; Phylogeny; protozoální proteiny; kinetochory; fylogeneze; Chromosome Segregation; segregace chromozomů; Kinetochores